Penguatan Tata Kelola Keuangan Badan Layanan Umum dalam Meningkatkan Nilai Publik: Analisis Strategic Triangle pada Pendidikan Penerbangan Indonesia: (Strengthening the Financial Governance of Public Service Agencies to Enhance Public Value: A Strategic Triangle Analysis of Indonesian Aviation Education) - Dian Wahyudin Wahyudin (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2026)
This study aims to critically analyze the financial governance of Public Service Agencies (BLU) in improving public service performance, focusing on aviation education institutions under the Ministry of Transportation in Indonesia. Although BLUs are granted financial flexibility, existing studies indicate that such flexibility has not been effectively translated into improved service quality. This research employs a qualitative case study approach, utilizing in-depth interviews, document analysis, and limited observations. Data were analyzed thematically using the Strategic Triangle framework, which consists of public value, legitimacy and support, and operational capacity. The findings reveal that financial flexibility has not been optimally transformed into public value creation. This is primarily due to weak financial governance, particularly in performance-based planning, limited human resource capacity, and the lack of integrated financial information systems. Furthermore, the study identifies an imbalance among the dimensions of the Strategic Triangle, where operational capacity remains weak, legitimacy is not substantively integrated, cross-sectoral stakeholder support requires further strengthening, and public value is suboptimal. This study concludes that strengthening financial governance through an integrative and balanced Strategic Triangle approach is essential to improving public service performance. The novelty of this research lies in integrating financial governance analysis with the Strategic Triangle framework in the under-researched context of aviation education BLUs in Indonesia. Keywords: Public Service Agency; Financial Governance; Public Service; Strategic Triangle; Public Value